2014
DOI: 10.1021/bc5002455
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Bioconjugation of Heterobifunctional Adaptors for Versatile Assembly of Bispecific Targeting Ligands

Abstract: High-throughput generation of bispecific molecules promises to expedite the discovery of new molecular therapeutics and guide engineering of novel multifunctional constructs. However, high synthesis complexity and cost have hampered the discovery of bispecific molecules in drug development and biomedical research. Herein we describe a simple solid-phase bioconjugation procedure for preparation of Protein A(G,L)-PEG-Streptavidin heterobifunctional adaptors (with 1:1:1 stoichiometry), which enable self-assembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Both Abs, anti-Her2 and anti-CD3, were assembled on the Protein A–PEG–streptavidin adaptor described in Section 2.3.3. to form the bispecific Ab. Flow cytometry assays confirmed that the Ab bispecific construct was able to target both Her2-positive human breast cancer SKBR3 cells in combination with CD3-positive human peripheral blood mononuclear cells, which served as the effector cells 199. Therefore, the CD3xHer2 bispecific Ab had an effect on T cell-mediated lysis of Her2-positive breast cancer cells.…”
Section: Functional Supramolecular Protein Nanostructures (Pns) and Tmentioning
confidence: 71%
See 4 more Smart Citations
“…Both Abs, anti-Her2 and anti-CD3, were assembled on the Protein A–PEG–streptavidin adaptor described in Section 2.3.3. to form the bispecific Ab. Flow cytometry assays confirmed that the Ab bispecific construct was able to target both Her2-positive human breast cancer SKBR3 cells in combination with CD3-positive human peripheral blood mononuclear cells, which served as the effector cells 199. Therefore, the CD3xHer2 bispecific Ab had an effect on T cell-mediated lysis of Her2-positive breast cancer cells.…”
Section: Functional Supramolecular Protein Nanostructures (Pns) and Tmentioning
confidence: 71%
“…Thus, it is intuitive that the formation of trimeric or oligomeric heteroproteins would require much more synthetic efforts. Nevertheless, there has been some recent breakthrough with the development of solid phase preparation of protein nanoarchitectures 19,20,199. Solid phase protein synthesis approaches have been devised to desymmetrize homomeric protein building blocks such as (strept)avidin 19,20.…”
Section: Design Principles Of Supramolecular Protein Nanostructures (mentioning
confidence: 99%
See 3 more Smart Citations